NEGERI SEMBILAN: RANTAU MINANGKABAU DI SEMENANJUNG TANAH MELAYU - Omar, Rahilah; Nelmawarni, - (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2008)
For a long time, the people of Minangkabaus have had strong inclination to leave their original village in search of new settlement besides seeking wealth. In the Minangkabau culture, this practice of leaving one’s home is known as merantau. This practice has caused a strong influence in terms of history, blood ties and cultural linkages especially between the Kingdom of Pagaruyung of Sumatra and Negeri Sembilan and in general the Minangkabaus. The existence of Negeri Sembilan began with the coming of the Minangkabaus perantau to the place. They explored the area and built settlements within these localities. Their roles as pioneer settlers and setting new localities are seen as one of the important aspects in the history of Negeri Sembilan. The Minangkabaus perantau did not only struggle to achieve a better living but had also successfully established a kingdom and instilled the Adat Pepatih as the cultural basis of Negeri Sembilan.